Operational Optimization at Screening Points During a Nuclear Disaster - Li, Hengyang; Oba, Kyoko; Numada, Muneyoshi (Faculty of Geography, Universitas Gadjah Mada, 2025)
In nuclear disaster scenarios, residents near affected areas may need to evacuate as the situation escalates. During the initial phase of evacuation in the Fukushima Daiichi Nuclear Power Plant accident following the Great East Japan Earthquake, approximately 20% of evacuees from restricted zones failed to undergo mandatory radiation screening. Niigata Prefecture, Japan, has established a manual for screening point management. However, the framework lacks a systematic examination of multifactorial variables affecting implementation under diverse nuclear disaster scenarios. To protect the public from exposure to radioactive substances released during a nuclear disaster, this study investigates the operational optimization of screening points through stay time modeling. For the considered evacuation scenario, simulations on the effects of the number of evacuees and the number of lanes installed (i.e., inspection capacity) are conducted. The results demonstrate a significant stay time reduction. The optimization criteria for the simulation are presented and the optimal number of lanes for mitigating radiation exposure risk is determined. This modeling approach provides quantitative evidence for optimizing screening point operations, which is particularly crucial during early-phase evacuations when radiation levels peak. The findings contribute to emergency response planning by establishing a framework for balancing evacuation efficiency with thorough radiation screening requirements.Received: 2024-05-24 Revised: 2025-02-25 Accepted: 2025-04-03 Published: 2025-05-26